2014
DOI: 10.1021/jp504387p
|View full text |Cite
|
Sign up to set email alerts
|

High-Coverage Oxygen-Induced Surface Structures on Ag(111)

Abstract: Surface structures formed by exposing Ag(111) to atomic oxygen have been studied by X-ray photoelectron spectroscopy, scanning tunneling microscopy, and density functional theory calculations. From the combination of the experimental and theoretical results, a model is proposed for the 0.5 ML oxygen coverage with a c(4 × 8) periodicity. Moreover, we find that a bulk-like Ag 2 O phase starts to form at coverages above 0.5 ML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 35 publications
8
80
0
Order By: Relevance
“…Calculations show that the several surface oxides and reconstructions have similar surface free energies, and they are more stable than O sub around 600 K (5,20,49), therefore, O sub desorbs before decomposition of the surface reconstruction. This behavior is qualitatively similar to subsurface H (H sub ) on Ni(111), where H sub is metastable with respect to adsorbed H (H ad ) and desorbs at around 100 K lower temperature than H ad (50)(51).…”
Section: Surface Temperature Effect On Oxygen Uptake On Ag(111)mentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations show that the several surface oxides and reconstructions have similar surface free energies, and they are more stable than O sub around 600 K (5,20,49), therefore, O sub desorbs before decomposition of the surface reconstruction. This behavior is qualitatively similar to subsurface H (H sub ) on Ni(111), where H sub is metastable with respect to adsorbed H (H ad ) and desorbs at around 100 K lower temperature than H ad (50)(51).…”
Section: Surface Temperature Effect On Oxygen Uptake On Ag(111)mentioning
confidence: 99%
“…Ag(111) surfaces exhibit a variety of different surface reconstructions induced by adsorbed oxygen (O ad ) (5,9), along with several other oxide species (10)(11)(12)(13)(14)(15)(16). The primary motivation to study the O/Ag(111) system is silver's importance as an industrial partial oxidation catalyst (11,17).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29]32 Other methods were also utilized for atomic oxygen delivery onto the Ag(111) surface under UHV conditions, such as NO 2 decomposition 31,36,38,40,47,50 and thermal gas cracking. 41,42,45 Ozone decomposition is an extremely efficient method for dosing high concentrations of oxygen atoms on metal surfaces under UHV conditions (i.e., in the absence of elevated-pressure exposures). Efficient atomic oxygen delivery onto single-crystal model catalyst surfaces with ozone was successfully carried out for Al(111), 51 Pd(111), 52 Pt(111), 52,53 and Au(111).…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 In a related study, Martin et al deposited atomic oxygen on Ag(111) by thermal cracking of O 2 (g) at 500 K with P O 2 = 10 −7 mbar. 41 They reported bulklike silver oxide formation at high θ O and argued that the c(4×8) overlayer is the precursor state for bulklike silver oxide formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Oxygen induced reconstructions of the Ag surface have been studied intensely since the 1970s when Rovida et al observed a (4 × 4) structure with LEED after high pressure O 2 dosing [24][25][26]. In the forty years since, a variety of models for a p(4 × 4)-O/Ag structure were proposed and dismissed [27]. Ultimately a model consisting of six triangles containing six Ag atoms each was proposed [21,28].…”
Section: Introductionmentioning
confidence: 99%